Characteristics and Consequences of Red Bed Bleaching by Hydrocarbon Migration: A Natural Example From the Entrada Sandstone, Southern Utah - Lydia R. Bailey; Henrik Drake; Martin J. Whitehouse; Peter W. Reiners (Geochemistry, Geophysics, Geosystems, 2022)
Abstract Extensive regions of yellow and white (“bleached”) sandstones within the terrestrial Jurassic red bed deposits of the Colorado Plateau reflect widespread interaction with subsurface reduced fluids which resulted in the dissolution of iron‐oxide grain coatings. Reduced fluids such as hydrocarbons, CO2, and organic acids have been proposed as bleaching agents. In this study, we characterize an altered section of the Slick Rock member of the Jurassic Entrada Sandstone that exposes bleached sandstone with bitumen‐saturated pore spaces. We observe differences in texture, porosity, mineralogy, and geochemistry between red, pink, yellow, and gray facies. In the bleached yellow facies we observe quartz overgrowths, partially dissolved K‐feldspar, calcite cement, fine‐grained illite, TiO2‐minerals, and pyrite concretions. Clay mineral content is highest at the margins of the bleached section. Fe2O3 concentrations are reduced up to 3× from the red to gray facies but enriched up to 50× in iron‐oxide concretions. Metals such as Zn, Pb, and rare‐earth elements are significantly enriched in the concretions. Supported by a batch geochemical model, we conclude the interaction of red sandstones with reduced hydrocarbon‐bearing fluids caused iron‐oxide and K‐feldspar dissolution, and precipitation of quartz, calcite, clay, and pyrite. Localized redistribution of iron into concretions can account for most of the iron removed during bleaching. Pyrite and carbonate stable isotopic data suggest the hydrocarbons were sourced from the Pennsylvanian Paradox Formation. Bitumen in pore spaces and pyrite precipitation formed a reductant trap required to produce Cu, U, and V enrichment in all altered facies by younger, oxidized saline brines.